Families and Social Security - Hans Fehr; Manuel Kallweit; Fabian Kindermann (Center for Economic Studies and ifo Institute (CESifo), 2015)
The present paper quantifies the importance of family insurance for the analysis of social security. We therefore augment the standard overlapping generations model with idiosyncratic labor productivity and longevity risk in that we account for gender and marital status. We simulate the abolition of pay-as-you-go pension payments, calculate the resulting intergenerational welfare changes and isolates aggregate efficiency effects for singles and families by means of compensating transfers. In accordance with previous studies that take into account transitional dynamics, we find that abolishing social security creates significant efficiency losses. Most importantly, however, we show that singles are substantially worse off from a shut-down of old-age payments compared to married couples. A decomposition of the efficiency loss reveals that this difference can be almost exclusively attributed to the insurance role of the family with respect to longevity risk. Since a married individual inherits her spouse's wealth after his death and the likelihood that both partners reach a very old age is relatively small, marriage serves as an insurance device against longevity risk for the surviving partner.
Keywords: J12; J22; 330; stochastic general equilibrium; home production; family insurance